Post-seismic velocity changes following the 2010 Mw 7.1 Darfield earthquake, New Zealand, revealed by ambient seismic field analysis. Issue 2 (30th January 2018) - Heckels, R EG; Savage, M K; Townend, J
Summary: Quantifying seismic velocity changes following large earthquakes can provide insights into fault healing and reloading processes. This study presents temporal velocity changes detected following the 2010 September M w 7.1 Darfield event in Canterbury, New Zealand. We use continuous waveform data from several temporary seismic networks lying on and surrounding the Greendale Fault, with a maximum interstation distance of 156 km. Nine-component, day-long Green's functions were computed for frequencies between 0.1 and 1.0 Hz for continuous seismic records from immediately after the 2010 September 04 earthquake until 2011 January 10. Using the moving-window cross-spectral method, seismic velocity changes were calculated. Over the study period, an increase in seismic velocity of 0.14 ± 0.04  per  cent was determined near the Greendale Fault, providing a new constraint on post-seismic relaxation rates in the region. A depth analysis further showed that velocity changes were confined to the uppermost 5 km of the subsurface. We attribute the observed changes to post-seismic relaxation via crack healing of the Greendale Fault and throughout the surrounding region.